2014
DOI: 10.1159/000362673
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acquiring Potentially Drug-Resistant Pathogens in Immunocompetent Patients with Pneumonia Developed Out of Hospital

Abstract: Background: The concept of healthcare-associated pneumonia (HCAP) exists to identify patients infected with highly resistant pathogens who are exposed to the healthcare environment. However, many studies have included immunosuppressed patients who were excluded from the original concept. Objectives: The risk factors of potentially drug-resistant (PDR) pathogens in patients with pneumonia developed outside the hospital were reevaluated after excluding the patients who had immunosuppression. Methods: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Table 1 shows risk factors associated with CAP owing to MDRO. 72,75,76 No consensus exists as to which is the most reliable combination of risk factors predicting the likelihood of patients hospitalized for CAP owing to MDROs. Brito and Niederman 77 reviewed several studies that evaluated patients with HCAP and proposed an algorithm that combined severity of illness and number of risk factors.…”
Section: Staphylococcus Aureus Including Methicillin-resistant Staphymentioning
confidence: 99%
“…Table 1 shows risk factors associated with CAP owing to MDRO. 72,75,76 No consensus exists as to which is the most reliable combination of risk factors predicting the likelihood of patients hospitalized for CAP owing to MDROs. Brito and Niederman 77 reviewed several studies that evaluated patients with HCAP and proposed an algorithm that combined severity of illness and number of risk factors.…”
Section: Staphylococcus Aureus Including Methicillin-resistant Staphymentioning
confidence: 99%
“…Also, new ATS/IDSA guidelines stated that HCAP could be included in the upcoming CAP guidelines because patients with HCAP frequently presented from the community and were initially cared for in emergency departments [4]. Several studies revealed that HCAP and drug-resistant bacterial pneumonia may not share identical risk factors for PDR pathogens, and the broad-spectrum antibiotic treatment targeting PDR pathogens in patients with HCAP may not be adequate and can even lead to overtreatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for multidrug-resistant pathogens are dealt with more extensively in another review in this series but are strongly linked to age; multimorbidity; comorbidities such as respiratory disease, dementia, and renal failure; and antibiotic use. [33][34][35]…”
Section: What Is Community-acquired Pneumonia?mentioning
confidence: 99%